Antibioprophylaxis in Prevention of Endophthalmitis in Intravitreal Injection: A Systematic Review and Meta-Analysis. - Cédric Benoist d'Azy; Bruno Pereira; Geraldine Naughton; Frédéric Chiambaretta; Frédéric Dutheil (PLoS ONE)
Despite endophthalmitis being the most feared complication, antibioprophylaxis remains controversial in intravitreal injections. Therefore, we conducted a systematic review and meta-analysis on the effects of antibioprophylaxis in intravitreal injections in the prevention of endophthalmitis. The PubMed, Cochrane Library, Embase and Science Direct databases were searched for studies comparing groups with and without antibiotics in intravitreal injection, with the use of the following keywords: "antibiotic*", "endophthalmitis" and "intravitreal injection*". To be included, studies needed to specify number of participants and number of endophthalmitis within each group (with and without antibiotics). We conducted meta-analysis on the prevalence of clinical endophthalmitis including both culture-proven and culture negative samples. Nine studies were included. A total of 88 incidences of endophthalmitis were reported from 174,159 injections (0.051% i.e., one incidence of endophthalmitis for 1979 injections). Specifically, 59 incidences of endophthalmitis were reported from 113,530 injections in the group with antibiotics (0.052% or one incidence of endophthalmitis for 1924 injections) and 29 incidences of endophthalmitis from 60,633 injections in the group without antibiotics (0.048% or one endophthalmitis for 2091 injections). Our meta-analysis did not report a significant difference in the prevalence of clinical endophthalimitis between the two groups with and without topical antibiotics: the odds ratio of clinical endophthalimitis was 0.804 (CI95% 0.384-1.682, p = 0.56) for the antibiotic group compared with the group without antibiotics. In conclusion, we performed the first large meta-analysis demonstrating that antibioprophylaxis is not required in intravitreal injections. Strict rules of asepsis remain the only evidence-based prophylaxis of endophthalmitis. The results support initiatives to reduce the global threat of resistance to antibiotics.